Lifecycle assessment modeling and encouraging reuse in the corrugated packaging industry using persuasion and operant conditioning - Ketkale, Harshwardhan, author; Simske, Steve, advisor; Miller, Erika, committee member; Conrad, Steven A., committee member; Cleary, Anne, committee member (Colorado State University. Libraries, 2023)
Greenhouse gas emission is a major contributor to climate change and global warming. Many sustainability efforts are aimed at reducing greenhouse gas emissions. These include recycling and the use of renewable energy. In the case of recycling, the general population is typically required to at least temporarily store, and possibly haul, the materials rather than simply throwing them away. This effort from the general population is a key aspect of recycling, and in order for recycling to work, some investment of time and effort is required by the public. In the case of corrugated cardboard boxes, it has been observed that there is less motivation for the general population to recycle them. Also, the manufacturing of a product such as a corrugated cardboard box (CCB) includes the extraction of a variety of raw materials in addition to supply chain efforts to get the raw materials to the industry. The extraction of raw material and its supply chain as well as the unproper end of lifecycle phase can significantly impact the carbon emission of a product over its lifecycle. This research explores different means of motivating people to reuse, and not just recycle, with different types of incentives. It addresses the use of persuasion techniques and operant conditioning techniques together to incentivize the general population to adopt sustainable efforts. Further, this study makes an attempt to segment the general population based on age, gender, persuasion preferences, operant condition preferences, personality types, awareness of environment/climate change as well as current recycling effort of the participants to use different forms of incentives and motivational work unlike any approaches found in the literature review. Four types of persuasion techniques and four types of operant conditioning are combined to give 16 different types of incentives. Three online surveys are conducted, and their data are analyzed (using entropy, Hamming distance, t-test, chi-square, and ANOVA). The results indicate that "positive reinforcement + ethos" is a cost-effective way to incentivize the general population. This study also conducts a Lifecycle Assessment (LCA) that gives the carbon emission of each phase of the product and a quantitative estimate of the overall product carbon footprint and its effect on the environment. This gives impetus to recommendations for improving the phases of the lifecycle to minimize carbon emissions. This research uses LCA to evaluate the carbon emission in each phase of the lifecycle of a typical 1 kg corrugated cardboard box in the United States. Carbon emission for the proposed "reuse" phase is also calculated, and the results are compared. To examine if the incremental cost of reusing the CCBs is less than the environmental and economic cost of reducing the extraction and supply chain of raw materials, this study explores the economic feasibility of the proposed "reuse" method that incentivizes the general population to reuse the CCBs instead of recycling or landfilling them. Economic tools such as willingness-to-pay vs. marginal cost curves and benefit-cost analyses are used to evaluate economic feasibility. The results indicate that the "reuse" method for CCBs is economically and environmentally feasible. It also supports the approach of using analytics, economics, and LCA to create a model that can be used for other products and processes as an evaluative process to determine if businesses can benefit from the reduction (or removal) of material extraction costs from the supply chain. The results of this study can be applied to a wide range of applications such as solar panels, incentives for vaccination, and other areas wherein sustainability-centric behavior is encouraged.
Keywords: incentives; motivation; reuse; lifecycle assessment; corrugated cardboard box; recycle